Penerapan Restorative Justice dalam Kasus Penadahan Melalui Facebook Marketplace di Kejaksaan Negeri Buleleng - Claudia Magdalena Ritonga; Made Sugi Hartono; I Wayan Lasmawan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims (1) examine the implementation of restorative justice by the Buleleng District Prosecutor's Office in cases of receiving stolen goods (penadahan) committed through the Facebook Marketplace platform, with a primary focus on the application of restorative justice despite the loss value exceeding the threshold set by prevailing laws and regulations; and (2) identify the considerations used by the Buleleng District Prosecutor’s Office in applying restorative justice to cases of receiving stolen goods conducted via Facebook Marketplace. The research adopts an empirical juridical method with a descriptive approach. Participants were selected purposively using purposive sampling. Data collection techniques included direct observation, interviews with relevant parties, and a review of legal documents, which were then analyzed qualitatively.The findings indicate that (1) resolution through Restorative Justice remains possible even if the loss exceeds IDR 2,500,000, as long as all substantive requirements stipulated in Prosecutor's Regulation Number 15 of 2020 are fulfilled. The decision to terminate prosecution in this case was based on considerations of justice for the victim and the fact that the perpetrator’s level of culpability was not considered severe; and(2) the victim did not object to the act of receiving stolen goods and prioritized the return of their motorcycle, which was successfully recovered in its original condition. The victim also supported the peace process and did not file charges against the alleged receiver.